PI(4)P recruits CIDE proteins to promote the formation of unilocular lipid droplets during adipogenesis and hepatic steatosis - Jin Wu; Mingming Gao; Xiaoqin Wu; Yang Liu; Taiping Zhang; Yan Liang; Haixia Yang; Chengxin Ma; Youpi Ye; Chunmei Chang; Peng Li; Feng-Jung Chen; et al. (Proceedings of the National Academy of Sciences, 2025)
Lipid droplets (LDs) are evolutionarily conserved organelles that play important roles in metabolism. Each LD is enclosed by a monolayer of phospholipids, distinct from bilayer membranes. The composition of LD surface phospholipids and their impact on LD growth and function remain to be defined. Phosphoinositides mark cellular organelles and regulate organellar function. Here, we demonstrate that PI(4)P decorates a subset of LDs to recruit and activate CIDE proteins. Enhanced expression of ORP2 and ORP5, LD-associated lipid transfer proteins that remove PI(4)P from LDs, abolished the localization and function of CIDE proteins. Blocking the synthesis of PI(4)P on the LD surface via knocking down PI4K2A also impaired the localization and function of CIDE proteins. In adipocytes, depleting PI(4)P dramatically reduced the size of LDs, as well as adipose tissue mass. In severe steatotic liver, depleting PI(4)P impeded LD enlargement. Our results thus identify a key function of LD surface PI(4)P under physiological conditions and unveil how CIDE proteins are recruited to LDs.